"Burgundy wine" pleural effusion: An unusual manifestation of acute bacterial empyema. Issue 2 (23rd February 2022) - Kuwahara, Daichi; Okazaki, Akihito
Abstract: Although empyema diagnosis by thoracentesis is relatively straightforward, the pleural effusion can sometimes be bloody rather than purulent. We report a case of acute empyema with a dark‐red bloody effusion, wherein multiple anaerobic bacteria were detected. Chest imaging findings improved with pleural drainage, intrapleural fibrinolytic therapy, and intravenous antibiotic treatment. Abstract : This image report presents a case of acute bacterial empyema with a dark‐red "Burgundy wine" pleural effusion. In cases of empyema secondary to lung abscess accompanied by internal bleeding, the pleural effusion may be bloody rather than purulent.